Organizational Entrepreneurship and Innovation at Medical Sciences Universities of Iran - Abolghasem Arabioun; Kambeiz Talebi; Reza Dehghan (Tehran University of Medical Sciences, 2012)
Background and Aim: This study aimed to assess the factors affecting organizational innovation and entrepreneurship at medical sciences universities in Iran. Such universities provide a wide range of services and products including prevention (hygiene), treatment (medical care), rehabilitation and palliative care, as well as their important mission, i. e., higher education and research in related fields. Materials and Methods: In this study, the researchers developed and examined a model for organizational innovation and entrepreneurship, including 16 factors classified into structure, content (behavior) and context (periphery) of the subject. The data collection instrument was a pre-structured questionnaire containing 58 core questions on the Likert scale. The validity of the questionnaire was computed by elites, and its reliability was estimated using Cronbach's Alpha (94%). Of 389 questionnaires, 325 were collected and their data were analyzed by SPSS software, version 18.Results: The three factors -- structural (structure), behavioral (content) and peripheral (context) -- which affect innovation and entrepreneurship are not favorable at medical universities.Conclusion :This study shows that structural, behavioral and peripheral factors are the most important, which affect innovation and organizational entrepreneurship at medical sciences universities.